Wage Differences between the Private and the Public Sector in Serbia: Some Evidence from Survey Data - Kosovka Ognjenović (The Vienna Institute for International Economic Studies (wiiw), 2011)
In this paper is estimated the wage gap between the public and the private sector in Serbia, for women and men separately. The results show that, with advance of the transition, the public sector generates wage premium for those who work in that sector compared to the employed in the private sector. The public sector overpaid both men and women compared to their counterparts in the private sector, but the estimated wage premium for women is lower compared to the estimated wage premium for men (22.3 percent and 25.4 percent, respectively; both estimates are statistically significant). The only group of workers who are penalized for working in the public sector is comprised of women and men who have higher education. In order to estimate the sectoral wage gap by gender several regression models were used the quantile regressions, the pooled OLS regression and the fixed-effects panel data model. The data that are used in the analysis are taken from the Serbian Living standard measurement surveys for 2003 and 2007
Keywords: J21; J31; J38; P2; 330; transition; wage differences; public and private sectors; living standard measurement survey data